Een doorbreking van orde: De betekenis van vertrouwen en geloof voor veiligheid - van Steden, Ronald (Religie & Samenleving, 2013)
This paper discusses the relationship between security and public order. In so doing, it first presents a review of critical literature on the role security (defined as ‘securitas’) plays within a capitalist or neoliberal system. Although such analyses are quite useful for disentangling violent discourses underlying western society, they are also too negative and one-sided to offer avenues for a new approach. Therefore, the second part of this paper explores a more positive outlook on security (defined as ‘certitudo’) that is grounded in social connectedness, trust and faith.